As rugas de um rosto: experiência e produção de sentido - Soares, Bruna Mayo (2015)
This study assumes that contemporary cultural context intensifies a whole struggle for controlling of time. As a result of this scene, in order to belong to a society in which this idea prevails, individuals resort to keep their body as an inclusion strategy, mainly respect to wrinkle s convergence in their his face. It refers to something previously designed by the group, which in turn construct clear consequences on physiological territory and marketing areas. So, to identify the effects and the persistence of wrinkles in a face, both physiological as well in marketing spheres belonging to the refered context, the objectives for this research were postulated for literature and also in a case study, belonging to three stages of discussion: the recognition of concepts including those proposed by the Semiotics of Culture, foccusing confluence of time and memory; giving an special importance to psychological features, as for instance narcisism, and finally the consideration on biological and anthropological role of wrinkles of a face, into some special and cultural universe; from another perspective we think about a characterization of how demand is configured to follow its consequent performance ,taking on procedures of the cosmetical industry, as it is presented in a previous context. In developing our aims, it highlights some authors like Giorgio Agamben, Iuri Lotman, Didier Anzieu, Andre Green and Philip Kotler, whose thoughts can explain and help to understand the complexity of wrinkles in a face, which is presented as an object, capable to give a certain and special trend to this research